Chinese nutrition therapy : dietetics in traditional Chinese medicine (TCM) - Kastner, Jörg, 1963- (Thieme, 2004)
Kastner's Chinese Nutrition Therapy is an excellent introduction to Chinese dietetics for both, students and practitioners of Chinese medicine. - I wholeheartedly endorse his book. Nigel Wiseman For millennia, the Chinese have taught that a healthy, appropriate diet is an integral part of maintaining good health and healing myriad disorders, from the common cold and morning sickness to heart disease and diabetes.